Tacrine-Coumarin Derivatives as Topoisomerase Inhibitors with Antitumor Effects on A549 Human Lung Carcinoma Cancer Cell Lines - Konkoľová, Eva; Hudáčová, Monika; Hamuľaková, Slávka; Jendželovský, Rastislav; Vargová, Jana; Ševc, Juraj; Fedoročko, Peter; Kožurková, Mária (Molecules (Basel, Switzerland), 2021)
A549 human lung carcinoma cell lines were treated with a series of new drugs with both tacrine and coumarin pharmacophores (derivatives 1a-2c) in order to test the compounds' ability to inhibit both cancer cell growth and topoisomerase I and II activity. The ability of human topoisomerase I (hTOPI) and II to relax supercoiled plasmid DNA in the presence of various concentrations of the tacrine-coumarin hybrid molecules was studied with agarose gel electrophoresis. The biological activities of the derivatives were studied using MTT assays, clonogenic assays, cell cycle analysis and quantification of cell number and viability. The content and localization of the derivatives in the cells were analysed using flow cytometry and confocal microscopy. All of the studied compounds were found to have inhibited topoisomerase I activity completely. The effect of the tacrine-coumarin hybrid compounds on cancer cells is likely to be dependent on the length of the chain between the tacrine and coumarin moieties (1c, 1d = tacrine-(CH2)8-9-coumarin). The most active of the tested compounds, derivatives 1c and 1d, both display longer chains.
Keywords: Topoisomerase I Inhibitors; proteiny vázající poly-ADP-ribosu; A549 Cells; DNA-topoisomerasy typu II; Drug Screening Assays, Antitumor; DNA; inhibitory topoisomerasy I; takrin; Tacrine; DNA Topoisomerases, Type II; topoisomerases I, II; screeningové testy protinádorových léčiv; DNA Topoisomerases, Type I; inhibitory topoisomerasy II; Cell Proliferation; Tumor Cells, Cultured; tacrine-coumarin derivatives; Antineoplastic Agents; A549; cytotoxicity; Coumarins; protinádorové látky; Humans; kumariny; DNA-topoisomerasy I; lung carcinoma cells; Topoisomerase II Inhibitors; molekulární struktura; proliferace buněk; Poly-ADP-Ribose Binding Proteins; buňky A549; nádorové buňky kultivované; lidé; Molecular Structure